Pre-pregnancy and prenatal care risk factors for spontaneous premature delivery in Western Uganda: a hospital based unmatched case-control study - Byonanuwe, Simon; Ssebuufu, Robinson; Oguttu, Benson; Nzabandora, Emmanuel (International Journal of Scientific Reports, 2021)
Background: We aimed to establish pre-pregnancy and prenatal care risk factors for spontaneous premature delivery at Kampala international university teaching hospital (KIUTH) so as to enable us draw a platform upon which specific interventions can be formulated. Methods: This was a hospital based unmatched case-control study conducted in the months of March to June 2019. A total of 110 cases and 330 controls admitted at KIUTH maternity and postnatal units were enrolled into the study. Interviewer administered questionnaires and respondent’s medical records were used to collect data. Chi square test and multiple logistic regression analysis were performed to establish the risk factors for spontaneous premature delivery at this facility. All data analyses were done using SPSS statistics version 20. Results: Nulliparity, previous premature delivery, history of premature rupture of membranes, previous cervical procedures, history of not having received preconception care, urinary tract infections during pregnancy and maternal obesity were independently associated with spontaneous premature delivery at this hospital. Conclusions: Guided by these factors, a high index of suspicion for spontaneous premature delivery among all pregnant women attending prenatal care is vital towards ameliorating this obstetric complication at KIUTH.